1989
DOI: 10.1002/hon.2900070402
|View full text |Cite
|
Sign up to set email alerts
|

Determination of proliferative fractions detected by immunohistochemistry with the monoclonal antibodies to bromodeoxyuridine and Ki‐67 in malignant lymphomas

Abstract: The stainability of proliferating cells with monoclonal antibodies to both bromodeoxyuridine (BrdU) and Ki-67 were compared in 22 malignant lymphomas and six related conditions. A significant correlation was observed (r = 0.78) between the positivities of proliferating cells determined using these two monoclonal antibodies. The growth fractions determined with the antibodies were usually related to the histologic classification, but labelling index was more varied in diffuse large cell type lymphoma. BrdU labe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0
1

Year Published

1991
1991
1996
1996

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 24 publications
1
12
0
1
Order By: Relevance
“…9,11,13,14,17,19 Using flow cytometry and cell suspensions from paraffin-embedded tissue, some authors have demonstrated a correlation between the S-phase fraction and prognosis in NHL. 13,19 A correlation of these data with the Kiel classification showed that the S-phase fraction correlated strongly with Kiel grades, with a mean value of 7.3% for low grade lymphomas and 15.6% for high grade.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…9,11,13,14,17,19 Using flow cytometry and cell suspensions from paraffin-embedded tissue, some authors have demonstrated a correlation between the S-phase fraction and prognosis in NHL. 13,19 A correlation of these data with the Kiel classification showed that the S-phase fraction correlated strongly with Kiel grades, with a mean value of 7.3% for low grade lymphomas and 15.6% for high grade.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we correlated the proliferative activity and cytomorphologic subclassification of the lymphomas based on the updated Kiel classification. 26 Although recent reports have described a correlation between cell proliferation and lymphoma grading, 9,11,13,14,17,19 to our knowledge this is the first published report on a study using PCNA on FNA material.…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…These techniques include cell suspensions such as [3H]-thymidine (Silvestrini et al, 1989;Veneroni et al, 1988) or bromodeoxyuridine (Brd U) (Kawauchi et al, 1989;Sasaki et al, 1988;Schrape et al, 1987) labelling indices, or flow cytometric measurement of DNA content (Baisch and Gerdes, 1987;Bauer et af., 1986;Braylan and Benson, 1989;Christensson et al, 1989;Roos et al, 1985). They also concern histological sections such as counts of mitoses (Akerman et al, 1987;Donhijsen, 1987) or nucleolar organizer regions (Schrape et ai., 1987;Crocker and Nar, 1987;Hall et al, 1988a) or the counting of cells expressing a nuclear antigen present during the cell cycle (G 1, S, G2, M) as revealed by the monoclonal antibody Ki-67 (Veneroni et al, 1988;Schrape et al, 1987;Baisch and Gerdes, 1987;Hall et al, 1988a;Gerdes et al, 1983Gerdes et al, , 1984aGerdes et al, , b, 1987Hall et al, 1988b;Cibull et al, 1989;Drach et al, 1989;Schonk et al, 1989;Shirono et al, 1989;Weinberg, 1989;Weiss et al, 1987).…”
Section: Introductionmentioning
confidence: 99%